Development of a numerical technique for modelling of multi-stage hydraulic fracturing in shale reservoirs - Sobhaniaragh, Behnam (2017)
Production efficiency from low permeable unconventional reservoirs demands promoting techniques including horizontal well drilling and multi-stage Hydraulic Fracturing (HF) stimulation. What significantly affects the fractures arrangement, and associated geometries is the stress field changes, referred to as “stress shadowing”. In this dissertation, in order to present a numerical technique, which is capable of capturing the non-planar hydraulically driven crack propagation with unpredictable path, on one hand, and tackling the feasible emergence of multiple cohesive cracks in a porous medium with fracture process zone at the crack tip, on the other hand, the Cohesive segments method in combination with Phantom Node Method, termed CPNM, is established. This numerical framework is implemented into a finite element analysis package (ABAQUS) along with user-defined subroutines. Considering a quasi-brittle multi-layer shale, two key scenarios including sequentially and simultaneously multi-stage HF from an individual wellbore are investigated. Validation of the numerical technique has been performed by comparing the solution for an individual fracture with a Khristianovic-Geertsma-de Klerk (KGD) solution and double fractures in the presence of stress shadowing. Afterwards, the analysis is extended to two lateral horizontal wellbores. The main contribution of this part is the detailed investigation of the stress shadowing effects as a function of the fracture spacing at various HF design in adjacent lateral wellbores. A particular attention is devoted to MZF design with the aim of mitigating side-effects of stress shadowing and enhancing the far-field fracture complexity, leading to introducing a modification to MZF design, termed M2ZF. The results obtained are shedding light on the advantages of the MZF and in particular M2ZF in the activation of pre-existing planes of weakness and natural fractures through stress shadowing effects.